Pimpinellin Inhibits Collagen-induced Platelet Aggregation and Activation Through Inhibiting Granule Secretion and PI3K/Akt Pathway - Liu, Gang; Yuan, Zhaowei; Tian, Xiaoyun; Xiong, Xiuqin; Guo, Fang; Lin, Zihan; Qin, Zhen (Frontiers in Pharmacology, 2021)
Pimpinellin is a coumarin-like compound extracted from the root of Toddalia asiatica. Its effects on platelet function has not been investigated. This study found that pimpinellin pretreatment effectively inhibited collagen-induced platelet aggregation, but did not alter ADP- and thrombin-induced aggregation. Platelets pretreated with pimpinellin showed reduced α granule (CD62) level and secretion of dense granule (ATP release). Pimpinellin-treated platelets also exhibited decreased clot reaction and TxB2 production. Pimpinellin pretreatment suppressed adhesion and spreading of human platelets on the fibrinogen coated surface. Analysis of tail bleeding time of mice administered with pimpinellin (40 mg/kg) revealed that pimpinellin did not change tail bleeding time significantly, number of blood cells, and APTT and PT levels. Pimpinellin inhibited collagen-induced ex vivo aggregation of mice platelets. Immunoblotting results showed that pimpinellin suppressed collagen-induced phosphorylation of PI3K-Akt-Gsk3β and PKC/MAPK in platelets.